KOMPARASI PENAFSIRANAYAT AL-QUR’AN DAN HADITS TENTANG KEPEMIMPINAN WANITA - Hanif A’la Ilhami; Zul Efendi; Arsal Arsal (Journal of Indonesian Comparative of Syari'ah Law, 2025)
This paper aims to compare two points of view in interpreting verses and hadiths related to women's leadership in Islam. This research is qualitative in nature, using literature sources. Scholars interpret verses and hadiths related to leadership with a clear and detailed methodology, including understanding the text and context of each. The distinction of Islamic teachings towards men and women is natural. However, both still lead to glory and paradise, even though their roles are different. Feminists reject the pattern of male leadership over women for various reasons. The existing teachings are not the true teachings of Islam, but the result of social constructs that can change over time. Based on the analysis that has been presented, the interpretation of the ulama is more accurate and stronger because it has a clear methodology and is supported by so many hadith narrations. In contrast, feminist thought is dominated by contextual interpretations without a clear methodology, which can lead to radical changes in religion.